Preferences and Perceived Effectiveness of Information Sources for Livestock Production - Sharma, Preeti; Aparna, (Indian Journal of Extension Education, 2021)
The present study analysed the preferences of dairy farmers for information, its sources and effectiveness of various media to disseminate knowledge about livestock production technologies among dairy farmers in Punjab. The data was collected during September 2019 fair held at Punjab Agricultural University, Ludhiana from purposively selected 120 farmers having dairy cattle. Information need of respondents was highest for disease control methods. Training camps and mobile phones were considered easily available information sources as well as were the most preferred information sources. Nearly half of the respondents very frequently consulted Veterinary Inspectors (VIs) for animal health problems while a large majority of respondents contacted KVK scientists very frequently followed by VIs for seeking knowledge regarding livestock production. Dairy farmers perceived training as the most effective source to acquire knowledge on dairy farming technologies followed by field veterinarians/VOs. It can be concluded that the extension agents should approach dairy farmers through trainings as farmers considered it the most effective information source.
Keywords: Information source; Preference; Livestock production; Training